2004
DOI: 10.1103/physrevlett.93.145301
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat of Disordered SuperfluidHe3

Abstract: The specific heat of superfluid 3 He, disordered by a silica aerogel, is found to have a sharp discontinuity marking the thermodynamic transition to superfluidity at a temperature reduced from that of bulk 3 He. The magnitude of the discontinuity is also suppressed. This disorder effect can be understood from the Ginzburg-Landau theory which takes into account elastic quasiparticle scattering suppressing both the transition temperature and the amplitude of the order parameter. We infer that the limiting temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
5
30
0
Order By: Relevance
“…16 and compared with the calculations of Sharma and Sauls. 53) For these data they found 35) a best fit value of ¼ 150 nm. Evidence for gapless behavior can also be found in the low temperature magnetic susceptibility, 18,30,57) the thermal conductivity, 74) and the attenuation of sound.…”
Section: Specific Heat Thermal Conductivity Gaplessnessmentioning
confidence: 99%
See 4 more Smart Citations
“…16 and compared with the calculations of Sharma and Sauls. 53) For these data they found 35) a best fit value of ¼ 150 nm. Evidence for gapless behavior can also be found in the low temperature magnetic susceptibility, 18,30,57) the thermal conductivity, 74) and the attenuation of sound.…”
Section: Specific Heat Thermal Conductivity Gaplessnessmentioning
confidence: 99%
“…Later analysis by Haard,25) based on independent measurements of the magnetization, confirmed the earlier conclusions. Additionally, Sprague et al found very little inhomogeneous broadening of their spectra, in inferred from specific heat measurements of Choi et al 35) compared with calculations from the HISM. The non-zero spectral weight at the Fermi energy is attributed to overlapping bound states.…”
Section: Nmr and Magnetizationmentioning
confidence: 99%
See 3 more Smart Citations